Computer-Mediated-Communication Perspectives on Telemedicine Integrated-Antenatal-Care Program during the New Habit Era - Prita Suci Nurcandrani (ULTIMA Comm, 2022)
Intervention of Integrated ANC Program of Puskesmas Purwokerto Utara II was commenced since stunting rate increased up to 13.58%. This incident plus pandemic situation have changed IEC pattern activities between the Puskesmas and pregnant women living in its working area. The problem is how midwives reach pregnant women through the ANC telemedicine program. Qualitative-descriptive method and data triangulation sources were used. CMC telemedicine in the ANC program studied from the perspectives of impersonal, interpersonal, and hypersonal communication uncover different findings. The results are not absolutely the key to the success of the program. Research from other perspectives are still needed.